Sosialisasi Pembentukan Karakter Religius - Zahro, Lyana; Komalasari, Poja Sanadhia; Hanif, Ahmad; Adinugraha, Hendri Hermawan; Setiawan, Drajat (Presisi Jurnal Pengabdian Masyarakat, 2023)
Character education is very important to instill, shape and develop national character values. Because education does not only educate students to become intelligent human beings with high intellectuals, it also builds individuals with noble character. National education functions to develop capabilities and shape the nation's character and civilization in educating the nation's life. National education aims to develop human potential that has faith and piety to God. material on the formation of religious character. The implementation is carried out in three stages, the first stage is the preparation stage. conduct a preliminary survey to see conditions in the field to coordinate early on the implementation of socialization activities on the formation of religious character. The purpose of this socialization activity is to increase knowledge of religious character formation to increase the character of MTS Salafiyah Wiradesa students. The material given during the socialization of the formation of religious character can go through stages including understanding, methods, values, benefits and application in life, the presenters provide explanations andexamples of each method of forming religious character